Dynamical behaviours of the (3+1)-dimensional Kadomtsev-Petviashvili equation describing the dispersive waves - Tariq, Kalim U.; İnç, Mustafa; Zubair, Muhammad (Springer, 2022)
In this study, some new soliton solutions to the (3+1)-dimensional Kadomtsev-Petviashvili equation describing the propagation of weakly dispersive waves in plasma, have been constructed analytically. The observed results are very encouraging and provide a powerful tool for analyzing the analytical solutions to nonlinear models emerging in the current generation of science and technology. The 3D, 2D and contours plots are drawn to demonstrate the physical nature of the nonlinear model by setting appropriate values to the arbitrary constants. The reported structures are bright, explicit, periodic, and combined wave solutions, which have been successfully demonstrated. Such approach can help to develop a better understanding for the dynamical behaviour of nonlinear structures and may also be applied to a variety of other complex models of recent era.
Keywords: The solitary wave solutions; The Kadomtsev-Petviashvili equation; The extended Kudryashov method; Analytical solutions